2020
DOI: 10.9758/cpn.2020.18.1.136
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 Gene: Its Effects on the Neuropsychological Functions in Patients with Opioid Use Disorder Undergoing Methadone Maintenance Treatment

Abstract: Objective: Patients with opioid use disorder (OUD) have impaired attention, inhibition control, and memory function. The aldehyde dehydrogenase 2 (ALDH2) gene has been associated with OUD and ALDH2 gene polymorphisms may affect aldehyde metabolism and cognitive function in other substance use disorder. Therefore, we aimed to investigate whether ALDH2 genotypes have significant effects on neuropsychological functions in OUD patients undergoing methadone maintenance therapy (MMT). Methods: OUD patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…ALDH2 is one of the major ALDH isozymes that catalyze the oxidation of dopamine. Impairment or inactivation of ALDH2 would accumulate a higher level of toxic dopamine metabolite, consequently contributing to neurocognitive dysfunction [35,36]. Brain atrophy and AD biomarkers changes were also observed from Aldh2-/-mice model [37].…”
Section: Discussionmentioning
confidence: 94%
“…ALDH2 is one of the major ALDH isozymes that catalyze the oxidation of dopamine. Impairment or inactivation of ALDH2 would accumulate a higher level of toxic dopamine metabolite, consequently contributing to neurocognitive dysfunction [35,36]. Brain atrophy and AD biomarkers changes were also observed from Aldh2-/-mice model [37].…”
Section: Discussionmentioning
confidence: 94%
“…The rs671 A allele may cause low ALDH2 enzyme activity and reduced metabolism, resulting in delayed clearance of drugs and increased plasma drug concentrations. ALDH2 is an important factor in opioid-use disorder and is associated with neuropsychological performance after methadone maintenance therapy [ 42 ]. There is thus compelling evidence indicating a role for ALDH2 rs671 in drug dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Twin (and other) studies suggested that most shared genetic and environmental factors may not be substance-specific [ 45 , 46 , 47 , 48 , 49 ], although genome-wide association studies often implicate genes involved in substance metabolism and subjective responses to specific drugs [ 50 , 51 ]. Identified genetic variants in addiction-related genes (e.g., aldehyde dehydrogenases [ ALDHs ], Gamma-Aminobutyric Acid Type A Receptor Alpha2 Subunit [ GABRA2 ], and DRD2/Ankyrin repeat and kinase domain containing 1 [ ANKK1 ]) were linked to dependence on various substances [ 52 , 53 , 54 , 55 ]. Gene network analysis showed immune signaling and extracellular signal-regulated protein kinases 1 and 2 ( ERK1/2 ) as novel genetic markers for multiple addiction phenotypes including alcohol, tobacco, and opioid use disorders [ 56 ].…”
Section: Introductionmentioning
confidence: 99%